A Mediterranean port-city in crisis: the case of Beirut - Nadine Hindi (City, Territory and Architecture)
Abstract The devastating explosion at Beirut port in August 2020, rated as the most powerful non-nuclear explosion of the twenty first century, not only destroyed the port but also significantly altered the city's identity and function as a port city. It destroyed the port infrastructure and has considerably limited its operational capacity. The aftermath context of the explosion has ignited an ongoing discussion on Beirut's identity as a port-city and serves as the point of departure for this article. Reflections on the future role of the port bring to light the implications of its urban history in relation to its geographic and political context. This article traces the rise of Beirut into a major port-city while highlighting the factors that caused its decline, revealing the complex systems that intertwined its growth to broader regional dynamics. While recognizing its growth in relation to the geo-political specificities, this article ultimately aims at exploring the nature of the future relationships between this Eastern Mediterranean port, the city, the hinterland, and its role in the broader network of maritime corridors in a rapidly changing global environment. In the context of its current local challenges and the shifting global dynamics, it addresses the role and the identity of Beirut as port-city, constantly shaped throughout its history. It articulates the dual crisis challenging the port in the aftermath of the explosion, examining the local response and the global approach within the evolving landscape of maritime trade corridors.